(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the realm of cultural writers, Bernard Malamud is regarded as a prolific American-Jewish writer. For, Malamud universalizes the Jewish way of life, portraying the mirthful life and perception of the Jews. The racial conflicts encountered by the Jews are put forth through a protagonist in his novel, thus, the character acquires the traits and vanishes the limitations kept on a Jewish character ever since. This paper discusses Malamud’s unique way of dealing with the racial conflicts faced by the Jews and breaks the stereotypical shackles of the Jews in the literary universe. It appreciates Malamud’s use of parody of cultural fanaticism among the liberals. The instigation of racial animosity between two men of two different races connects them with writing that is creating art. It apprehends the thematic involvement in the novel, racial conflicts, and as well as penetrates into the real world with the existing approaches. Explores the inherent political strategy using the multiculturalism technique and exposes the bourgeois’ stereotypical objectivity of intelligence based on the race and culture.